ANALYSIS OF CURRENCY FLUCTUATIONS AND SELECTED AGRICULTURAL EXPORT COMMODITIES IN NIGERIA - NKONGNKANG, MICHEAL O; EFA , EYAMBA GLORY; AMOKE, CHUKWUNONSO VALENTINE; ANAKWUE, ESTHER CHIOMA; AKADILE, IFEANYI ALEXANDER (JOURNAL OF ECONOMICS AND ALLIED RESEARCH, 2025)
The theory of comparative advantage of David Richardo has made it clear that no economy can exist in isolation hence the need to optimize gain from international trade wherein economies of the world could build international trade competitiveness based on area of advantage. The impact of currency fluctuations on selected agricultural export commodities is an effort to unravel the currency fluctuation dynamics of international trade on export commodities. Data for five major agricultural export commodities was sourced from the Food and Agricultural Organisation (FAO) and World Bank Development Indicator database. The result indicates that a unit appreciation of the currency produced a 0.002 unit decline in cocoa-bean export in Nigeria in the short run. Currency fluctuation however had no significant effect on rubber export either in the long or short term. The outcome of the study also shows that a unit rise in the value of the local currency resulted in a 0.03 unit rise in the volume of palm-oil export, while it also increased groundnut export by 0.002 in the short term. Finally, a unit fall in the value of the local currency triggered a 0.049 unit fall in cotton seed export in Nigeria. Generally, the study found that currency fluctuations have a small quantitative impact on the selected agricultural export commodities in Nigeria. The study recommends that Nigerian government should adopt a more rigorous export promotion strategy with direct bearing on improving the competitiveness of exportable especially as the economy tries to break away from oil export dominance